2023
DOI: 10.3390/v15081676
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Viruses in Nosocomial Pneumonia: An Evolving Paradigm

Abstract: Nosocomial pneumonia (NP) represents a leading cause of morbidity and mortality in hospitalized patients. Historically, clinicians have considered hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP), which comprise NP, to be essentially bacterial processes. As such, patients suspected of having either HAP or VAP are initially treated with broad-spectrum antibiotics, and few clinicians search for a possible culprit virus. Recent reports which build on earlier studies, however, indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Its use as a marker of microbiological cure has therefore never been evaluated. Some preliminary study suggests, for both CAP and HAP, that viral-bacterial coinfection may have prognostic impact not only in influenza or SARS-CoV2 infections but also for other respiratory viruses [46][47][48]. Finally, the consequences of systematic screening of a viral co-infection in mPCR has not been evaluated either.…”
Section: Discussionmentioning
confidence: 99%
“…Its use as a marker of microbiological cure has therefore never been evaluated. Some preliminary study suggests, for both CAP and HAP, that viral-bacterial coinfection may have prognostic impact not only in influenza or SARS-CoV2 infections but also for other respiratory viruses [46][47][48]. Finally, the consequences of systematic screening of a viral co-infection in mPCR has not been evaluated either.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, in a recent meta-analysis, authors found that the incidence rate of VAP in patients with TBI varies widely between studies, from 21% to 60%, with higher rates of early-onset VAP episodes comparing to the late-onset VAP subtype. Moreover, in the same study there have been described several independent risk factors for VAP occurrence, such as smoking, tracheostomy, blood mass transfusion at hospital admission time, diabetes or high values of injury severity score (ISS) [ 10 ]. Another imperative and debatable factor to discuss is that some studies suggest the impact in differentiating VAP in ventilated traumatized patients with trauma-associated pneumonia (TAP), still being unclear if the same diagnostic criteria of VAP used as in non-traumatic patients would significantly change the incidence rate in this population.…”
Section: Relevant Sectionsmentioning
confidence: 99%